(untitled) (Research, Society and Development, 2019)
The aim of this study was to know the meanings of care attributed by workers who work in a Long Term Care Institution for the Elderly to institutionalized people with mental disorders. Qualitative study conducted in a Long-term Care Institution for the Elderly in the interior of Rio Grande do Sul. 19 semi-structured interviews were conducted with workers from June to September 2015, respecting the ethical principles of the National Health Council. Thematic categories proposed by Minayo emerged from the following categories: meanings attributed to care to the person with mental disorder and meaning of care related to daily challenges. The results showed perceptions of care focused on humanization, encouraging the autonomy of people with mental disorders, and also care based on control and monitoring. There was also evidence of a theoretical-practical unpreparedness of the worker for mental health care. It is concluded that care is perceived by the workers of the institution under study in a polysemic way, and still needs theoretical and practical deepening regarding mental health issues.